Intervención urbano-arquitectónica del mercado mayorista de la ciudad de Latacunga - Mata Molina, Byron Stalin (2026)
This study focuses on an urban and architectural analysis of the wholesale market in the parish of Eloy Alfaro, in the canton of Latacunga, province of Cotopaxi. This area faces serious mobility problems during market days, especially on Eloy Alfaro Avenue (formerly Panamericana E35) and Buenos Aires Street, the main roads connecting the province of Pichincha with the urban center of Latacunga. In addition, it is a consolidated area, characterized by major facilities, including the Technical University of Cotopaxi and various educational institutions. It also has a commercial and industrial sector along with residential areas, which contributes to high vehicle and pedestrian traffic. This analysis identified a lack of green areas, which generates urban problems due to a lack of spare space, visual and environmental pollution, the formation of islands of color, and poor waste management that ends up in nearby rivers. Likewise, the lack of maintenance has caused the metal structure to rust, the roofs to wear out, and the masonry to crack and fall off. There is no adequate assessment of vehicular traffic on internal roads, leading to conflicts in vehicular circulation without prioritizing pedestrians. There are no adequate external stops for public transportation, which makes it difficult for citizens to get around. This proposal seeks to generate solutions for the wholesale market and the immediate environment, with an urban analysis that integrates green areas, spaces for social cohesion and recreation, bike lanes, and pedestrian walkways connecting the urban area with the market. The design considers the city's socio-cultural and economic environment, as well as its biophysical environment, human settlements, and mobility, and verifies the existing construction area through a formal and functional analysis of the structure.